1994
DOI: 10.1111/j.1469-7998.1994.tb04853.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and breeding cycle of the Australian sea lion Neophoca cinerea (Mammalia: Pinnipedia)

Abstract: Surveys of the Australian sea lion Neophoca cinerea were conducted throughout its range in Western and South Australia between December 1987 and February 1992. Almost every island was visited between Houtman Abrolhos and The Pages (n = 255), many of them more than once. Sea lions breed on at least 50 islands, 27 in Western Australia and 23 in South Australia. Of the 50 breeding sites, 31 have not been reported previously. A further 19 islands may also support breeding colonies. A total of 1,941 pups was counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 20 publications
2
76
1
Order By: Relevance
“…Although most Australian sea lion colonies are found in isolated areas or on coastal islands where unlicensed visits are prohibited, three South Australian colonies, Seal Bay, Seal Slide, and Cape Gantheaume, all on Kangaroo Island, experience high levels of human tourist activity and visitation (Gales et al 1994;Shaughnessy 1999). Several haul-outs (nonbreeding sites) in WA are also subject to very high levels of tourist visitation (Orsini et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most Australian sea lion colonies are found in isolated areas or on coastal islands where unlicensed visits are prohibited, three South Australian colonies, Seal Bay, Seal Slide, and Cape Gantheaume, all on Kangaroo Island, experience high levels of human tourist activity and visitation (Gales et al 1994;Shaughnessy 1999). Several haul-outs (nonbreeding sites) in WA are also subject to very high levels of tourist visitation (Orsini et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although their distribution is broad, individual colonies show limited dispersal, localized foraging by both sexes, and a high degree of population genetic structure (Lowther et al 2012(Lowther et al , 2013. Sea lions are indirectly exposed to terrestrial microorganisms through ingestion of seawater contaminated with wastewater runoff and via behaviors such as hauling-out on beaches used by humans (Gales et al 1994). In addition, as a tourist icon, sea lion colonies in both WA and SA receive high levels of human visitation, with visitor numbers to Seal Bay on Kangaroo Island exceeding 150,000 tourists annually .…”
Section: Introductionmentioning
confidence: 99%
“…This partly reflects the fact that the habitat requirements of the New Zealand sea lion are unknown, but Smith (1989) suggested that as both the Australian sea lion (Neophoca cinerea) and the South American sea lion {Otaria byronia) inhabit lower latitudes (Vaz-Ferreira 1981;Gales et al 1994), then it is possible that the New Zealand sea lion could as well.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, at a relatively small-scale, many frog species show higher synchrony when they breed in ponds and less synchrony when they breed in rivers (Vences et al 2002). At a larger spatial and taxonomic scale, all pinnipeds are strikingly synchronous in breeding across their collective familial range except for the Australian sea lion (Neophoca cinerea) that exhibits unique asynchronous breeding both between and within colonies (Gales et al 1994). Perhaps the broadest taxonomic and spatial scales that could be used to test our hypothesis would involve avian migration systems, where breeding synchrony tends to increase with latitude (Baker 1938;Spottiswoode & Møller 2004), usually because of increasingly short breeding seasons.…”
Section: Discussionmentioning
confidence: 99%